Impact of chronic exposure to trichlorfon on intestinal barrier, oxidative stress, inflammatory response and intestinal microbiome in common carp (Cyprinus carpio L.). (April 2020) - Chang, Xulu; Wang, Xianfeng; Feng, Junchang; Su, Xi; Liang, Junping; Li, Hui; Zhang, Jianxin
Abstract: Trichlorfon is an organic phosphorus pesticide used to control different parasitic infections in aquaculture. The repeated, excessive use of trichlorfon can result in environmental pollution, thus affecting human health. This study aimed to determine the effects of different concentrations of trichlorfon (0, 0.1, 0.5 and 1.0 mg/L) on the intestinal barrier, oxidative stress, inflammatory response and intestinal microbiome of common carp. Trichlorfon exposure significantly reduced the height of intestinal villus and decreased the expression levels of tight junction genes, such as claudin-2, occludin and ZO-1, in common carp. Moreover, the activities of antioxidant enzymes, such as CAT, SOD and GSH-Px, exhibited a decreasing trend with increasing trichlorfon concentrations, while the contents of MDA and ROS elevated in the intestinal tissues of common carp. The mRNA and protein levels of pro-inflammatory cytokines TNF-α and IL-1β were significantly upregulated by trichlorfon exposure. The level of anti-inflammatory cytokine TGF-β was remarkably higher in 1.0 mg/L trichlorfon treatment group compared to control group. In addition, the results demonstrated that trichlorfon exposure could affect the microbiota community composition and decreased the community diversity in the gut of common carp. Notably, the proportions of some probiotic bacteria, namely, Lactobacillus, Bifidobacterium and Akkermansia, were observed to be reduced after trichlorfon exposure. In summary, the findings of this study indicate that exposure to different concentrations of trichlorfon can damage intestinal barrier, induce intestinal oxidative damage, trigger inflammatory reaction and alter gut microbiota structure in common carp. Graphical abstract: Image 1 Highlights: Trichlorfon exposure reduced the height of intestinal villus and decreased the expression levels of tight junction genes. Trichlorfon exposure increased the levels of ROS and MDA and decreased the antioxidant enzyme activity. Trichlorfon exposure affected the intestinal microbiota community composition of common carp.